2022
DOI: 10.3390/ma15113988
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Janus MoSSe Monolayer Polymorph Modifications Using Density Functional Theory

Abstract: Two-dimensional transition metal dichalcogenides (TMDs) with Janus structures are attracting increasing attention due to their emerging superior properties in breaking vertical mirror symmetry when compared to conventional TMDs, which can be beneficial in fields such as piezoelectricity and photocatalysis. The structural investigations of such materials, along with other 2D materials, can be successfully carried out using the Raman spectroscopy method. One of the key elements in such research is the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…For example, the vibrational mode with the highest wavenumber value (404 cm −1 ) involves only half of the sulfur ions on each monolayer surface and, at the same time, the sulfur ions remain motionless on the opposite surface (see Figure S6a ). Such behavior is similar to the MoSSe Janus monolayers [ 85 ]. In this case, the vibration of only one side of the monolayer does not manifest itself as a strong, medium, or even weak Raman band.…”
Section: Resultssupporting
confidence: 64%
“…For example, the vibrational mode with the highest wavenumber value (404 cm −1 ) involves only half of the sulfur ions on each monolayer surface and, at the same time, the sulfur ions remain motionless on the opposite surface (see Figure S6a ). Such behavior is similar to the MoSSe Janus monolayers [ 85 ]. In this case, the vibration of only one side of the monolayer does not manifest itself as a strong, medium, or even weak Raman band.…”
Section: Resultssupporting
confidence: 64%
“…In this context, simulated IR and Raman spectra based on density functional theory (DFT) calculations can be helpful in understanding the vibrational properties of Li 2 MnO 3 . In fact, DFT-based theoretical studies have shown excellent agreement with experimental IR and/or Raman spectra of organic compounds [28], crystalline [29], and 2D materials [30].…”
Section: Introductionmentioning
confidence: 77%
“…TMDs with unlike chalcogen atoms (results in symmetry breaking) have been reported to improve/change the optical, electrical, and physicochemical characteristics in contrast to their pristine analogues. The presence of different chalcogen atoms in layered dichalcogenides also leads to inherent strain, , emanating from the difference in size of the chalcogen atoms giving rise to slightly bent layers . Improvement in the electrocatalytic performance, , photocatalytic water-splitting, and energy storage devices has been reported in the case of strained asymmetric TMDs (MoSSe) on account of high concentration of the active (edge) sites, , as well as enhancement in the electronic conductivity as compared to that of pristine sulfides and selenides.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, CM depends on the extent of induced polarization as well as on the extent of charge transfer between the substrate and the analyte. The magnitude of charge transfer depends on band alignment between the substrate and the analyte with available DOS on the substrate near the Fermi level. ,, MoSSe has been theoretically predicted to possess out-of-plane dipoles due to a difference in the size of S and Se. , This inherent polarization, as well as a high number of active sites and high electronic conductivity of 1T MoSSe over its homologues (MoS 2 /MoSe 2 ), may result in the improvement of charge-transfer characteristics together with polarization of the analytes, leading to an increase in the analyte cross-section for the enhancement in the Raman signal. Based on the above discussion, MoSSe (2H/1T) has been synthesized and investigated as SERS substrates and its characteristics compared with its pristine analogues (MoS 2 /MoSe 2 ).…”
Section: Introductionmentioning
confidence: 99%